UPAYA GURU DALAM MENINGKATKAN KETERAMPILAN BERBICARA NARASI PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI MOJOREJO 01 BATU - Vino Putra Hadiyani; Djoko Susanto; Zubad Nurul Yaqin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article focuses on the improvement of students’ narrative speaking skills in Indonesian learning at Class V of SDN Mojorejo 01 Batu. The study described in this article used qualitative research with an explanatory research design, which could be used to test and find out the relationship between one and other variables. The explanatory research design is intended to explain the relationship, difference, or influence of one variable with the research hypothesis, refine the theory, and examine the explanation of why something occurred. Qualitative research, which is descriptive data resulting in the research, referred to words, pictures, and behaviour that were described in the explanation more than numerical data presentment. The research stages covered (1) teacher planning in improving narrative speaking skills in Indonesian language learning for students of class V students, (2) implementing narrative speaking skills activities in Indonesian language learning for class v students, (3) implications of teacher efforts in improving narrative speaking skills for class v students in elementary school Mojorejo Country 01 Batu. Data collection techniques were interviews, observations, and documentation. In addition, data analysis techniques were data condensation, data presentation, and data verification. Whilst the research subjects involved the teachers and the students of Class V. The results of this study indicated that at first, the teacher planning improved narrative speaking skills such as materials, media, methods, and techniques. Secondly, implementation in improving the narrative speaking skills. For online learning, it began with the opening activities, preparing videos and pdfs, online learning via WhatsApp, and the adjusted use of zoom. For offline learning, it began with taking student books, submitting student assignments, and additional guidance for students facing the teacher directly. The roles of the teacher were a learning resource, facilitator, manager, demonstrator, supervisor, motivator, and evaluator. The implication or impact of improving narrative speaking skills produced a positive impact after the implementation of KBM (teaching and learning activities)